Pengaruh Halal Awareness dan Sertifikasi Halal pada Produk Kecantikan MS Glow terhadap Minat Beli Muslim Millennial - Venisa Ayu Syafira; Nur Diana; Harun Al Rasyid (El-Aswaq: Islamic Economics and Finance Journal, 2021)
This study aims to determine the effect of halal awareness and halal certification onMS Glow beauty product on purchase intention of Muslim Millennial. This type ofresearch is quantitative research. Sampling was done by using the non probabilitysampling with accidental sampling method. There are 102 respondents who areMuslim Millennial in Malang and using MS Glow beauty product. The analytical toolused is Multiple Linear Regression Analysis using SPSS 25. The result showed thatthe variable Halal Awareness (X1) had a positive and partially significant effect onpurchase intention (Y), halal certification (X2) had positive and significant effect onpartial to purchase intention (Y).